Balancing the books: how we can better support students who are parents. Issue 2 (4th March 2023) - Andrewartha, Lisa; Knight, Elizabeth; Simpson, Andrea; Beattie, Hannah
ABSTRACT: Striking a balance between being a parent and being a student can place heavy demands on time and energy. Many students who are parents have employment obligations and financial concerns which create additional barriers to success. Despite these difficulties, institutional support for students who are parents is often limited. Common challenges include accessing adequate on-campus childcare and parenting rooms, and scheduling study around care commitments. A distinct recognition of student parents has been largely missing from the Australian student equity space. To address this gap, we captured the first-hand accounts of 578 student parents through a national survey of their motivations, challenges, and strengths. Findings are analysed within the four stages of the Critical Interventions Framework – pre-access, access, participation, and attainment/transition out. Our article recommends new avenues of intervention to foster the success of student parents.